Study of genetic diversity and molecular variation in natural populations of Pinus armandii subsp. Xuannhaensis L.K. Phan - an endemic species in Son La, Vietnam using ISSR markers - Duy, Vũ Đình; Xuân, Bùi Thị Tuyết; Thảo, Đỗ Thị Phương; Lộc, Phan Kế; Tâm, Nguyễn Minh (Vietnam Journal of Biotechnology, 2016)
Pinus armandii subsp. xuannhaensis L.K. Phan is a new five needle pine discovered recently from Xuan Nha Nature Reserve, Son La province. This subspecies is considered as a narrow endemic to Vietnam and is assessed as endangered. In this study, 15 ISSR markers were used to analyze the genetic diversity of this taxon collected in five subpopulations (Tan Xuan, Thac Nuoc, Dinh VTV2, Near VTV2 and Dinh Pomu). Results of the analysis showed 15/15 markers were polymorphic. A total of 51 DNA fragments were amplified, in which 50 fragments were polymorphic (98.04%). Genetic diversity was the highest in Dinh Pomu subpopulation (I = 0.555; h = 0.8; PPB = 68.76%; Ne =1.6 and He = 0.4)) and the lowest in Tan Xuan subpopulation (I = 0.428; h = 0.6; PPB = 57.06%, Ne = 1.215 and He = 0.303). Analysis of molecular variance (AMOVA) results showed that the total level of molecular changes between subpopulations was 7% and between individuals in the same subpopulation was 93%. A constructed dendrogram based on similarity matrix of 71 Pinus armandii subsp. xuannhaensis L.K. Phan samples divided the samples into two main groups with genetic similarity coefficients ranged from 0.53 to 0.96. Results of the molecular analysis showed that Pinus armandii subsp. xuannhaensis L.K. Phan species should be protected at the population level.